Pengaruh pH Tanah Terhadap Metode Aerasi Dalam Stabilisasi Logam Berat Timbal (Pb2+) - Moch Shafansyah Yumna Argia; Muhammad Abdus Salam Jawwad (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This study examines the effect of soil pH variation on the effectiveness of the aeration method in stabilizing the heavy metal lead (Pb2+). Lead contamination from industrial waste and fossil fuels is a serious environmental problem as it is carcinogenic and can pollute ecosystems, including plants, posing a health risk to humans. Soil remediation is needed to address this issue, and soil aeration is one promising method. However, the effectiveness of aeration is highly influenced by soil environmental conditions, particularly pH, as low pH makes heavy metals easily soluble and mobile. This quantitative experimental study used 3 reactors with variations in pH treatment (acidic pH 4, neutral pH 6.5, and alkaline pH 10) and aeration duration (6 hours/day). Samples were analyzed using Atomic Absorption Spectrophotometry (AAS) to measure the remaining lead concentration, and the stabilization efficiency was calculated from the difference in concentration before and after treatment. The results showed that the alkaline pH treatment (pH 10) consistently provided the highest lead reduction efficiency, reaching 78.7% at a 24-hour aeration duration. Increasing the pH caused the Pb2+ ions to precipitate into insoluble and less toxic compounds. Statistical analysis using ANOVA confirmed that pH and aeration duration had a significant effect on the efficiency of lead (Pb2+) reduction.